2015
DOI: 10.1123/jpah.2012-0452
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Relaxation During and After Work are Independently Associated With the Need for Recovery

Abstract: Although prospective evidence is necessary to confirm the causal relationships, our findings suggest that engaging in stair climbing, leisure activities, (physical) detachment at work, relaxation and detachment after work is associated with a lower NFR. For future work site health promotion initiatives, interventions might be targeted at improving physical activity and relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…In one case (Coffeng et al, 2015) we used Comprehensive Meta-Analysis software 2.2 (Biostat, Inc, Englewood, NJ) to convert the reported unstandardized beta-weight into a correlation coefficient. We standardized the direction of correlation coefficients between studies to produce consistent meanings of effect sizes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one case (Coffeng et al, 2015) we used Comprehensive Meta-Analysis software 2.2 (Biostat, Inc, Englewood, NJ) to convert the reported unstandardized beta-weight into a correlation coefficient. We standardized the direction of correlation coefficients between studies to produce consistent meanings of effect sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Geurts and Sonnentag (2006) contrast internal recovery (i.e., within working time) and external recovery (i.e., after finishing daily work). Thus, detachment can occur during work breaks (Coffeng et al, 2015), in the afternoon (Sonnentag and Bayer, 2005), in the evening (Sonnentag and Fritz, 2007), at the weekend (Fritz et al, 2010a), or in a longer recovery period like vacation (de Bloom et al, 2013). In our study, we only focus on detachment from work during daily non-work time (afternoon, evening) as it is most frequently studied in this research domain (Sonnentag and Fritz, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the OFFICAIR participation rate seems to be in line with some of other recent surveys. The response rate was 26% in a Danish study assessing indoor environmental quality in dwellings (Frontczak et al, 2012a), and 35% in a study examining the associations between physical activity and relaxation and need for recovery in office workers (Coffeng et al, 2014). In addition, the participation rate of the OFFICAIR study seems acceptable for studies within worksites: Baruch and Holtom (2008) analyzed the response rates in studies published in the years 2000 and 2005 and concluded that the average response rate was 35.7% in organizational research.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some studies have observed that employees who report higher levels of psychological detachment, relaxation and control during this time of rest experience higher attention levels and less fatigue immediately after their break [42,43]. Additionally, employees who participated in restful activities during this period-socialising, taking a walk or a nap-felt more positive emotions and less negative emotions after their break [44,45]. On the other hand, employees who took part in work-related activities-e.g., preparing materials for a meeting-experienced a higher amount of negative emotions after their lunch break [46].There is a critical need for effective methods to reduce work-related stress that may be employed by a large number of people, are easily accessible and have few side effects, and can be self-directed…”
mentioning
confidence: 99%